2020
DOI: 10.1111/jcmm.14979
|View full text |Cite
|
Sign up to set email alerts
|

Modified level of miR‐376a is associated with Parkinson's disease

Abstract: Parkinson's disease (PD) is a frequent progressive neurodegenerative disorder. Impaired mitochondrial function is a major feature of sporadic PD. Some susceptibility or causative genes detected in PD are strongly associated with mitochondrial dysfunction including PGC1α, TFAM and GSK3β. microRNAs (miRNAs) are non‐coding RNAs whose altered levels are proven in disparate PD models and human brains. Therefore, the aim of this study was to detect modulations of miRs upstream of PGC1α, TFAM and GSK3β in association… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 35 publications
1
23
0
1
Order By: Relevance
“…Thus, we made use of MPP+ to induce neurotoxicity in cultured neuronal cells, to construct both acute and chronic in vitro PD models. Previous studies have shown that oxidative stress and apoptotic pathways are two principal mechanisms of MPP+‐induced cell death 2 , 19,20 . Consistently, here, treatment of SH‐SY5Y neuronal cells with 2000 µM MPP+ for 24 hours and 1000 µM over 2 weeks remarkably increased the percentage of apoptotic cells and ROS generation, confirming that complex 1 has been blocked efficiently by MPP+ in both models of PD in our study.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Thus, we made use of MPP+ to induce neurotoxicity in cultured neuronal cells, to construct both acute and chronic in vitro PD models. Previous studies have shown that oxidative stress and apoptotic pathways are two principal mechanisms of MPP+‐induced cell death 2 , 19,20 . Consistently, here, treatment of SH‐SY5Y neuronal cells with 2000 µM MPP+ for 24 hours and 1000 µM over 2 weeks remarkably increased the percentage of apoptotic cells and ROS generation, confirming that complex 1 has been blocked efficiently by MPP+ in both models of PD in our study.…”
Section: Discussionsupporting
confidence: 91%
“…Growing evidence also represents that there is a correspondence between peripheral blood and brain tissue, suggesting that evaluating disease‐relevant genes’ expression in peripheral blood can act as an advantageous proxy measure for gene expression in the CNS and reflect the state of illness in the brain 37 . PBMCs are deemed to be a peripheral laboratory providing a golden opportunity to study the mechanisms linked to NDDs and to find an indicator for their prognosis, diagnosis and treatment 12 , 19 . Accordingly, here, cell models of PD were developed to clarify whether miR‐193b and PGC‐1α/FNDC5/BDNF pathway are affected by oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MicroRNAs belongs to the class of small non-coding RNA (sncRNA) with a length of 17–22 nt. They inhibit gene expression level by binding to the 3’untranslated region (3’UTR) of mRNA, resulting in mRNA degradation, adenylation, or translational inhibition [ 39 ]. Over the past few years, various miRNAs target PD-related genes that induce neuroinflammation and accelerate the neurodegeneration of dopaminergic neurons ( Table 1 ).…”
Section: Epigenetics and Neuroinflammation In Pdmentioning
confidence: 99%
“… Role of microRNAs in Parkinson’s disease [ 28 , 52 , 54 , 63 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 ]. …”
Section: Figureunclassified